2005
DOI: 10.1016/j.febslet.2005.06.068
|View full text |Cite
|
Sign up to set email alerts
|

Signaling pathways of magnolol‐induced adrenal steroidogensis

Abstract: This study focused on identifying the signalling mediating the effect of magnolol on corticosterone production. Magnolol-induced corticosterone production was completely inhibited by mitogen-activated protein kinase kinase (MEK)-inhibitor PD98059, tyrosine kinase (TK)-inhibitor genistein or Janus tyrosine kinase 2 (JAK2)-inhibitor AG490, suggesting that extracellular signal-regulated kinase (ERK) and JAK2 are both involved in this signaling cascade. Further, magnolol induced the transient phosphorylation of ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
2
7
0
Order By: Relevance
“…Because of the potent biological actions of these cytokines, considerable attention has been focused on identifying the mechanisms that activate and limit cytokine gene expression. Only recently was it recognized that PA may signal through novel mechanisms, including the MAPK signaling network, which might be linked to transcription factor in the nucleus (Watanabe et al, 2004;Chen et al, 2005). Consistent with these findings, we and others have found that various kinases, including Akt and MAPKs can be activated by PA stimulation Lim et al, 2003;Li and Malik, 2005).…”
Section: Discussionsupporting
confidence: 74%
“…Because of the potent biological actions of these cytokines, considerable attention has been focused on identifying the mechanisms that activate and limit cytokine gene expression. Only recently was it recognized that PA may signal through novel mechanisms, including the MAPK signaling network, which might be linked to transcription factor in the nucleus (Watanabe et al, 2004;Chen et al, 2005). Consistent with these findings, we and others have found that various kinases, including Akt and MAPKs can be activated by PA stimulation Lim et al, 2003;Li and Malik, 2005).…”
Section: Discussionsupporting
confidence: 74%
“…The inhibitors, AG490, LY-294002, and IBMX, were respectively diluted in DMSO for stock solutions of 1mg/ml, 5mg/ml, and 0.5 M. A G-CSF receptor chimera (Fc Chimera Active) was purchased from Abcam (Cambridge, MA), and G-CSF was obtained from Loma Linda University Pharmacy; both were diluted in phosphate buffered saline. The following concentrations were used: cholera toxin (50 ng/ml) (Hsu et al, 2006); AG490 (50 μM) (Chen et al, 2005); LY-294002 (20 μM) (Williams et al, 2010); and IBMX (10 μM) (Montero-Hadjadje et al, 2006). A dose-response study of G-CSF (using 30, 100, and 300 ng/ml) (Hsu et al, 2006), and the G-CSF receptor chimera (at 10, 30, and 100 ng/ml) after cholera toxin treatment was conducted.…”
Section: Methodsmentioning
confidence: 99%
“…Animals were maintained according to the Guide for the Care and Use of Laboratory Animals set by Kaohsiung Medical University. Adrenal cell cultures were prepared as described by Chen, Chang, Chen, and Wang (2005). For the StAR promoter activity assay, Chinese hamster ovary cell line (CHO-K1) was used, which was kindly provided by Prof. Wen-Wei Chang (Chung-Shan Medical University, Taiwan).…”
Section: Cell Culturementioning
confidence: 99%
“…Cell viability was determined using the tetrazolium dye colorimetric test according to the procedure described by Chen et al (2005).…”
Section: Cell Viability Assaymentioning
confidence: 99%